2012
DOI: 10.3855/jidc.2105
|View full text |Cite
|
Sign up to set email alerts
|

Trends in neonatal and post-neonatal tetanus admissions at a Nigerian teaching hospital

Abstract: Introduction: Tetanus accounts for high morbidity and case fatality rates in developing countries. This study therefore aimed to identify reasons for the persistence of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
21
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 10 publications
10
21
1
Order By: Relevance
“…The case fatality rate (CFR) of tetanus in our study was 16.7%, this is comparable to the CFR of 18.2% and 18% reported by Oyedeji et al (2012) and Alhaji et al (2013) respectively. However, in a previous study carried out between 1995-2009 in UPTH by Yaguo-ide and Nte (2011) a higher CFR of 30.5% was reported, this may probably be attributed to better immunization coverage in the years after this study.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The case fatality rate (CFR) of tetanus in our study was 16.7%, this is comparable to the CFR of 18.2% and 18% reported by Oyedeji et al (2012) and Alhaji et al (2013) respectively. However, in a previous study carried out between 1995-2009 in UPTH by Yaguo-ide and Nte (2011) a higher CFR of 30.5% was reported, this may probably be attributed to better immunization coverage in the years after this study.…”
Section: Discussionsupporting
confidence: 83%
“…There was no significant sex difference in cases of tetanus seen in our study which contrasts with the reports from previous studies. Ojini and Danesi (2005), Oyedeji et al (2012), Oyelami et al (1996), Yaguo Ide and Nte (2011), Yaguo Ide and Nte (2012). AKI as a complication of tetanus was not seen in any of our patients however in the study carried out by Moura Filho et al ((2008) the prevalence of AKI was reported to be 11.8% while a higher prevalence of 34% was recorded by Hilton et (2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Post neonatal tetanus is an important problem in Nigeria [8] [9] [10] [11] [12]. Most studies have recognized tetanus beyond the neonatal period as a problem of enormous consequence with high case fatality rate [10] [13] [14], yet it is still seemingly disregarded and continues to afflict several children in this millennium [8] [12] [15].…”
Section: Introductionmentioning
confidence: 99%